ANALYSIS OF SALARY INCREASE AND LOYALTY TOWARDS THE PERFORMANCE OF POLRI MEMBERS AT THE WORK UNIT OF POLAIR PUSDIK LEMDIKLAT POLRI - Badarisman, Dudih; Taufik, Kemal; Hanaffy, Jamal (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to analyze the effect of salary increase and loyalty on the performance of members at the Pusdik Polair Lemdiklat Polri Work Unit. The phenomenon that underlies this study is the finding of Polri members with suboptimal performance levels, even though the policy of salary increase and performance allowances has been implemented. This study uses a quantitative approach with an associative research type. A sample of 50 respondents was determined through a simple random sampling technique from a population of 100 members. Data were collected using a closed questionnaire with a Likert scale, and analyzed using multiple linear regression with the help of the SPSS version 20 program. The results of the study indicate that partially and simultaneously, salary increase and loyalty have a positive and significant effect on member performance. This study emphasizes the importance of compensation management and loyalty development as a strategy to improve institutional performance.